Rolling Back Malaria : The World Bank Global Strategy and Booster Program - World Bank (Washington, DC, 2012)
This report translates the Bank's corporate commitment into increased efforts to control malaria. It lays the basis for a Booster Program for Malaria Control, through which the Bank will make an important contribution to malaria control in the years ahead. This effort will be undertaken in support of country-led programs, and in partnership with community service organizations, specialized agencies, and financiers of malaria control at all levels. Consistent with the new Global Strategic Plan of the Roll Back Malaria Partnership, the Bank's work will combine measures to increase coverage of malaria-specific interventions with effective service delivery, broader health-system development, and capacity building across multiple sectors. The new business model combines an emphasis on outcomes with flexibility in approaches. Products and services related to malaria control will be tailored to client segments, in order to meet the needs of countries, and deploy the Bank's comparative advantages, while strengthening collaboration with partner agencies, co-financiers, and civil society. In the short to medium term, the new Booster Program for Malaria Control will provide increased financing, and technical support to accelerate program design and implementation, increase coverage, and improve outcomes rapidly. Henceforth, malaria control will be mainstreamed into the Poverty Reduction Strategies, and large sector-development programs that emphasize outcomes.